2019
DOI: 10.1530/joe-18-0313
|View full text |Cite
|
Sign up to set email alerts
|

FSH inhibits AMH to support ovarian estradiol synthesis in infantile mice

Abstract: Anti-Müllerian hormone (AMH) regulates ovarian function in cyclic females, notably by preventing premature follicle-stimulating hormone (FSH)-mediated follicular growth and steroidogenesis. Its expression in growing follicles is controlled by FSH and by estradiol (E2). In infantile females, there is a transient increase in the activity of the gonadotrope axis, as reflected by elevated levels of both gonadotropins and E2. We previously demonstrated in mice that elevated FSH concentrations are necessary to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 45 publications
2
39
0
3
Order By: Relevance
“…In rodents, a similar transient FSH peak has been reported at ~12–14 days of postnatal life [95,96]. Remarkably at the same time (PN14), AMH is downregulated in preantral/early antral follicles of the first waves [56]. Using cultures of infantile mice ovaries, these authors have demonstrated the existence of a repressive action of FSH on AMH expression in preantral/early antral follicles of the first follicular waves.…”
Section: “Emerging” Roles Of Amh In the Neuroendocrine Control Of Repmentioning
confidence: 57%
See 1 more Smart Citation
“…In rodents, a similar transient FSH peak has been reported at ~12–14 days of postnatal life [95,96]. Remarkably at the same time (PN14), AMH is downregulated in preantral/early antral follicles of the first waves [56]. Using cultures of infantile mice ovaries, these authors have demonstrated the existence of a repressive action of FSH on AMH expression in preantral/early antral follicles of the first follicular waves.…”
Section: “Emerging” Roles Of Amh In the Neuroendocrine Control Of Repmentioning
confidence: 57%
“…The authors concluded that although the number of initial primordial follicles available immediately following birth was independent of the presence of AMH, it was an important factor in inhibiting follicular recruitment and thus AMH presence was essential for prolonging fecundity. AMH is already expressed in infantile ovaries in mammals [48,5156] and the findings from Garrel and colleagues in 2016 raised the intriguing hypothesis that AMH could play a critical role in the female pituitary gonadotropic activity during the infantile period [20]. This issue will be further discussed in section 4.…”
Section: Roles Of Amh In Postnatal Gonadsmentioning
confidence: 99%
“…31,32 The expression of these enzymes converts androstenedione synthesized from follicular theca cells into E2. Although studies have reported that FSH affects the development of preantral follicles, [33][34][35] there is no report regarding the effect of FSH on the growth pattern of preantral follicles in vitro. The reason may be that the PM follicles and ES follicles were cultured together in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cette étude révèle que les hauts niveaux de FSH de la mini-puberté répriment l'expression de l'AMH dans les follicules les plus matures, levant ainsi le frein inhibiteur de l'AMH sur la stéroïdogenèse [6]. (Hprt, hypoxanthine phosphoribosyltransferase).…”
Section: Resultsunclassified
“…Nos travaux ont montré que l'AMH était exprimée dans l'ovaire de souris avant la puberté ( Figure 1A), comme chez l'humain et chez d'autres espèces de mammifères [1,5]. Pour étudier l'action de l'AMH lors de cette période, nous avons effectué des cultures organotypiques d'ovaires de souris au stade mini-puberté (12-14 jours postnatals [jpn]) [6]. Les ovaires ont été traités par l'AMH en présence de fortes concentrations de FSH mimant ses niveaux circulants in vivo.…”
Section: Quel Est Le Rôle De L'hormone Antimüllerienne Dans L'ovaire unclassified